Analysis of behavioral sequences in social interactions of autistic children: a latent class model based on structured play observation - Chen, YiWen (Frontiers in Psychiatry, 2026)
ObjectiveThis study addresses the unclear dynamic mechanisms underlying social interactions in children with autism spectrum disorder (ASD) by constructing a structured play observation framework.MethodsBy combining latent class analysis (LCA) and temporal analysis techniques, this study systematically analyzed the heterogeneous characteristics of social behavioral sequences. Using a longitudinal tracking and cross-sectional design, multimodal data (video coding and physiological indicators) were collected from 60 children with ASD and 40 typically developing (TD) children.ResultsThe behavioral sequence complexity of the ASD group was significantly lower than that of the TD group, exhibiting an “avoidance–rigid” cyclical pattern. The LCA model identified three behavioral patterns: high interaction, medium interaction–rigid, and low interaction–high avoidance. The low interaction–high avoidance group demonstrated the poorest intervention response rate.ConclusionThis study innovatively applies dynamic systems theory to the ASD field, demonstrating that behavioral sequences can serve as intervention targets. It advances evaluation tools from static description to dynamic prediction, providing a scientific basis for personalized intervention planning. The integration of structured observation and multimodal data analysis deepens the understanding of the dynamic mechanisms underlying social impairments in ASD and holds significant theoretical and practical value.